Urban regions now & tomorrow. Between vulnerability, resilience and transformation. - (:unkn) unknown (Springer Fachmedien, 2017)
The book points to three dominant concepts of how to deal with long-term or surprising and also sudden catastrophic changes, with a main focus on resilience. It is dealing with past, current and future change processes in European, Northern American as well as Australian cities and urban regions, and with the challenges they pose to a resilient urban development. Additionally, contributions deal with potential transformations of urban and regional development and related planning and governance approaches.
Keywords: Stadtregion; Stadt; Stadtumland; Resilienz; Vulnerabilität; Klimawandel; Transformation; Nachhaltigkeit